Citrullination of Proteins as a Specific Response Mechanism in Plants - Marondedze, Claudius; Elia, Giuliano; Thomas, Ludivine; Wong, Aloysius; Gehring, Chris (Frontiers in Plant Science, 2021)
Arginine deimination, also referred to as citrullination of proteins by L-arginine deiminases, is a post-translational modification affecting histone modifications, epigenetic transcriptional regulation and proteolysis in animals, but has not been reported in higher plants. Here we report, firstly, that Arabidopsis thaliana proteome contains proteins with a specific citrullination signature and that many of the citrullinated proteins have nucleotide-binding regulatory functions. Secondly, we show that changes in the citrullinome occur in response to cold stress, and thirdly, we identify an Arabidopsis thaliana protein with peptidyl arginine deiminase activity, that was shown to be calcium-dependent for many peptide substrates. Taken together, these findings establish this post-translational modification as a hitherto neglected component of cellular reprogramming during stress responses.